On Addressing Practical Challenges For RNN-Transducer - Zhao, Rui; Xue, Jian; Li, Jinyu; Wei, Wenning; He, Lei; Gong, Yifan (Automatic Speech Recognition and Understanding Workshop, 2021)
In this paper, several works are proposed to address practical challenges for deploying RNN Transducer (RNN-T) based speech recognition systems. These challenges are adapting a well-trained RNN-T model to a new domain without collecting the audio data, obtaining time stamps and confidence scores at word level. We solve the first challenge with a splicing data method which concatenates the speech segments extracted from the source domain data. To get time stamps, a phone prediction branch is added to the RNN-T model by sharing the encoder for the purpose of forced alignment. Finally, we obtain word level confidence scores by utilizing several types of features calculated during decoding and from a confusion network. Evaluated with Microsoft production data, the splicing data adaptation method improves the baseline and adaptation with the text to speech method by 58.03% and 15.25% relative word error rate reduction, respectively. The proposed time stamping method can get less than 50 millisecond word timing difference from the ground truth alignment on average while maintaining the recognition accuracy. We also obtain high confidence annotation performance with limited computation cost.